Unjuk Kerja Turbin Air Kaki Angsa Next-G dengan Variasi Lebar Sudu dan Jumlah Kaki Sudu Menggunakan Pendekatan Komputasional - Hidayat, Muhamad Taufiq; Wulandari, Retno (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
This study to determine the efficiency of next-G geese foot turbine, the Angled Watermill is utilized in rural or remote areas, with potential rivers and local people to easily adapt the material. It is necessary to design a new turbine that can able to extract energy from free fluid flow or zero headwater power resources. The design and material of the design were done using Computational Fluid Dynamics (CFD) software. The method is to know the most optimal modification of goat water turbine design from the variation in width and number of feet of Next-G geese foot mill legs as follows: (1) 600; (2) 700 mm; (3) 750 mm, for the number of legs used 4 pieces, 6 pieces, 8 legs. The results of development the Next-G goose foot wheel mill blade is the momentÂ pressure value increased for the width of the water wheel blade 750 mm, and the momentÂ pressure decreases to 600 mm. The number of feet 4 blade the pressure moment is increased and decreasing for the number of feet of 8 blade. The optimum momentÂ pressure is applied to the width 750 mm waterwheel blade and the number of 4 impeller feet.